2016
DOI: 10.1123/jab.2015-0249
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Minimalist and Maximalist Footwear on Patellofemoral Kinetics During Running

Abstract: The current study aimed to comparatively examine the effects of minimalist, maximalist, and conventional footwear on the loads experienced by the patellofemoral joint during running. Twenty male participants ran over a force platform at 4.0 m×s-1. Lower limb kinematics were collected using an 8-camera motion capture system allowing patellofemoral kinetics to be quantified using a musculoskeletal modeling approach. Differences in patellofemoral kinetic parameters were examined using one-way repeated-measures AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 22 publications
2
65
1
Order By: Relevance
“…This finding is consistent with those in previous studies [20,21]. Sinclair and Esculier [7,8] reported that the body actively changed the lower limb strategy while wearing minimalist shoes, i.e., increased step rates, lowered foot inclination angle at foot strike and reduced knee maximum flexion angle and joint range of motion (ROM). Moreover, according to the equation for the knee joint angle and the patellofemoral joint contact area, a decreased knee ROM decreased the patellofemoral joint contact area during the stance phase of runners wearing minimalist shoes; this condition is adverse to the reduction of PFJS.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is consistent with those in previous studies [20,21]. Sinclair and Esculier [7,8] reported that the body actively changed the lower limb strategy while wearing minimalist shoes, i.e., increased step rates, lowered foot inclination angle at foot strike and reduced knee maximum flexion angle and joint range of motion (ROM). Moreover, according to the equation for the knee joint angle and the patellofemoral joint contact area, a decreased knee ROM decreased the patellofemoral joint contact area during the stance phase of runners wearing minimalist shoes; this condition is adverse to the reduction of PFJS.…”
Section: Discussionsupporting
confidence: 92%
“…Esculier [8] tested shoes with different MI with regards to running mechanics and observed that a higher MI shoe indicates a low foot inclination angle at foot strike and a low peak PFCF. Sinclair [7] compared minimalist, cushioned and maximalist shoes in terms of patellofemoral kinetics and observed that the knee ROM decreased when the runner was wearing minimalist shoes. Interestingly, the patellofemoral joint loads were greater with the low-MI shoes, i.e., maximalist shoes, than with the others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While research has yet to show the superiority of maximalist or minimalist shoes in preventing injuries, it is apparent that various types of footwear cause runners to run differently and shift loads to different body parts. 14 Greater running shoe cushioning tends to increase VLR [15][16][17] and knee joint forces, 18 but decrease ankle forces and peak foot pressure. Conversely, lower cushioning tends to shift initial foot contact closer to the midfoot or forefoot, thus decreasing VLR 19 and knee joint forces, [20][21][22] but increasing ankle forces and foot pressure.…”
Section: Introductionmentioning
confidence: 99%